Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To find \((f-g)(x)\), we need to subtract the function \(g(x)\) from the function \(f(x)\).
Given:
[tex]\[f(x) = 4x^3 + 6x^2 - 3x - 4\][/tex]
[tex]\[g(x) = 4x - 3\][/tex]
Now, we calculate \((f-g)(x)\):
[tex]\[ (f-g)(x) = f(x) - g(x) \][/tex]
[tex]\[ (f-g)(x) = (4x^3 + 6x^2 - 3x - 4) - (4x - 3) \][/tex]
To perform the subtraction, distribute the negative sign through \(g(x)\):
[tex]\[ f(x) - g(x) = (4x^3 + 6x^2 - 3x - 4) - 4x + 3 \][/tex]
Now, combine like terms:
- Combine the \(x^3\) terms:
[tex]\[ 4x^3 \][/tex]
- Combine the \(x^2\) terms:
[tex]\[ +6x^2 \][/tex]
- Combine the \(x\) terms:
[tex]\[ -3x - 4x = -7x \][/tex]
- Combine the constant terms:
[tex]\[ -4 + 3 = -1 \][/tex]
Thus, \((f-g)(x)\) becomes:
[tex]\[ (f-g)(x) = 4x^3 + 6x^2 - 7x - 1 \][/tex]
Matching this result to the given options:
A. \((f-g)(x) = 4 x^3 + 6 x^2 + x - 7\)
B. \((f-g)(x) = 4 x^3 + 6 x^2 + x - 1\)
C. \((f-g)(x) = 4 x^3 + 6 x^2 - 7 x - 1\)
D. \((f-g)(x) = 4 x^3 + 6 x^2 - 7 x - 7\)
The correct answer is:
[tex]\[ \boxed{C. (f-g)(x) = 4 x^3 + 6 x^2 - 7 x - 1} \][/tex]
Given:
[tex]\[f(x) = 4x^3 + 6x^2 - 3x - 4\][/tex]
[tex]\[g(x) = 4x - 3\][/tex]
Now, we calculate \((f-g)(x)\):
[tex]\[ (f-g)(x) = f(x) - g(x) \][/tex]
[tex]\[ (f-g)(x) = (4x^3 + 6x^2 - 3x - 4) - (4x - 3) \][/tex]
To perform the subtraction, distribute the negative sign through \(g(x)\):
[tex]\[ f(x) - g(x) = (4x^3 + 6x^2 - 3x - 4) - 4x + 3 \][/tex]
Now, combine like terms:
- Combine the \(x^3\) terms:
[tex]\[ 4x^3 \][/tex]
- Combine the \(x^2\) terms:
[tex]\[ +6x^2 \][/tex]
- Combine the \(x\) terms:
[tex]\[ -3x - 4x = -7x \][/tex]
- Combine the constant terms:
[tex]\[ -4 + 3 = -1 \][/tex]
Thus, \((f-g)(x)\) becomes:
[tex]\[ (f-g)(x) = 4x^3 + 6x^2 - 7x - 1 \][/tex]
Matching this result to the given options:
A. \((f-g)(x) = 4 x^3 + 6 x^2 + x - 7\)
B. \((f-g)(x) = 4 x^3 + 6 x^2 + x - 1\)
C. \((f-g)(x) = 4 x^3 + 6 x^2 - 7 x - 1\)
D. \((f-g)(x) = 4 x^3 + 6 x^2 - 7 x - 7\)
The correct answer is:
[tex]\[ \boxed{C. (f-g)(x) = 4 x^3 + 6 x^2 - 7 x - 1} \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.